PERAYAAN DEDIKASI GEDUNG GEREJA DAN ALTAR - Rahawarin, Bernard A. (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2015)
This article wants to emphasize that any church building is a home for the faithfull. A church should be a place where the faithful come together in order to listen to the word of God and to celebrate the memory of God’s wonderful work of salvation. A church building is essential to make the Church community as a temple of God visible in the factual world of human beings. To indicate how important the role of a church building, it must be ritually consecrated.